The textile reader - Hemmings, Jessica (New York Berg Publishers, 2012)
"The Textile Reader is the first anthology to address textiles as a distinctive area of cultural practice and a developing field of scholarly research. Revealing the full diversity of approaches to the study of textiles, the Reader introduces students to the theoretical frameworks essential to the exploration of the textile from both a critical and a creative perspective. Content is drawn from a wide range of genres - blogs, artists' statements and fiction, as well as critical writings - and organized in themed sections covering touch, memory, structure, politics, production and use. Each thematic section is separately introduced and concludes with a bibliography for further reading. The Textile Reader will be an invaluable resource for students of textile design, textile art, applied arts and crafts and material culture. Selected authors include Glenn Adamson, Anni Albers, Gilles Deleuze, Felix Guattari, Sarat Maharaj, Rozsika Parker, Sadie Plant, Peter Stallybrass, Alice Walker and Catherine de Zegher"--Provided by publisher.
Keywords: Textile fabrics